2020
DOI: 10.1021/acs.est.0c04257
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Chloride and Methyl Bromide Production and Consumption in Coastal Antarctic Tundra Soils Subject to Sea Animal Activities

Abstract: Methyl chloride (CH 3 Cl) and methyl bromide (CH 3 Br) are the predominant carriers of natural chlorine and bromine from the troposphere to the stratosphere, which can catalyze the destruction of stratospheric ozone. Here, penguin colony soils (PCS) and the adjacent tundra soils (i.e., penguin-lacking colony soils, PLS), seal colony soils (SCS), tundra marsh soils (TMS), and normal upland tundra soils (UTS) in coastal Antarctica were collected and incubated for the first time to confirm that these soils were C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…1 ). After being autoclaved, they switched to CH 3 Br and CH 3 Cl sources at 0.45 ng kg −1 hr −1 and 6.9 ng kg −1 hr −1 , respectively, supporting the conventional idea that soils act as a bi-directional interface of CH 3 Br and CH 3 Cl with simultaneous enzymatic degradation and abiotic production 5 , 12 , 18 . The deactivation of methyl halide-consuming microorganisms following heat treatment 19 in autoclaved soil results in the unidirectional interface of CH 3 Cl and CH 3 Br emissions, possibly catalyzed by endogenous Fe(III) in the soil 12 .…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…1 ). After being autoclaved, they switched to CH 3 Br and CH 3 Cl sources at 0.45 ng kg −1 hr −1 and 6.9 ng kg −1 hr −1 , respectively, supporting the conventional idea that soils act as a bi-directional interface of CH 3 Br and CH 3 Cl with simultaneous enzymatic degradation and abiotic production 5 , 12 , 18 . The deactivation of methyl halide-consuming microorganisms following heat treatment 19 in autoclaved soil results in the unidirectional interface of CH 3 Cl and CH 3 Br emissions, possibly catalyzed by endogenous Fe(III) in the soil 12 .…”
Section: Resultsmentioning
confidence: 56%
“…Flux calculation. CH 3 Br and CH 3 Cl fluxes from the samples were calculated based on the hourly averaged change of headspace concentration multiplied by moles of headspace air 5 , and normalized to the dry mass of the soil (ng kg −1 hr −1 ) or the volume of the seawater (ng L −1 hr −1 ); or were reported as the total mass of CH 3 Br and CH 3 Cl produced in pure chemical experiments (ng). Positive fluxes represented production of CH 3 Br and CH 3 Cl while negative fluxes represented consumption of CH 3 Br and CH 3 Cl from the headspace air.…”
Section: Incubations and Halocarbon Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, over this short time scale, the living soil accumulated significantly more CH3Br than the autoclaved soils. Other studies have observed that sterilization treatments significantly alter net CH3X flux from soils, affirming that biological processes dominate CH3X fluxes in situ 29,[38][39][40] .…”
Section: Resultsmentioning
confidence: 79%
“…Under extreme dry conditions, microbial metabolic activity is expected to be attenuated, thereby decreasing indicator gas production rates, while water saturated conditions are expected to hamper gas diffusion from soil pores to the headspace 51 . Natural CH3X fluxes in soils are also known to vary with temperature 40, 52 , hydration 47, 53 , organic matter content 29, 49 , halide concentration 17 , redox properties 39, 53 and microbiome 29, 40 . Additional studies are needed to understand how these processes affect total indicator gas accumulation in the headspace of different matrices.…”
Section: Resultsmentioning
confidence: 99%